Laser aided additive manufacturing of spatially heterostructured steels. (January 2022) - Tan, Chaolin; Chew, Youxiang; Weng, Fei; Sui, Shang; Ng, Fern Lan; Liu, Tong; Bi, Guijun
Abstract: Current heterostructured materials demonstrate the high potential to circumvent strength-ductility tradeoff but face challenges with unconfigurable hetero-zone distribution and mechanical anisotropy. This study explored laser aided additive manufacturing (LAAM) of non-laminar spatially heterostructured materials (SHM) with configurable architectures to combine superior properties from the constitutive AISI 420 stainless steel and C300 maraging steel to enhance the overall properties. It is proven that the hatch spacing ( h ) has a significant effect on the microstructural evolutions and mechanical properties of the SHMs as it affects the layer thickness and inter-dilution regions. The mechanical properties of the SHMs were evaluated at multi-scales. The sample with h of 1.5 mm possesses a high tensile strength of about 1.6 GPa along with a reasonable break elongation of 8.1%, showing a good strength-ductility combination. Micropillar compression tests were conducted to measure localised mechanical properties, which is critical to understand the strengthening mechanism. Additionally, the SHM substantiates a much higher strength than many lamellar and linear functionally graded materials reported in the literature. This can be explained by the rule-of-mixture effect and hetero-deformation induced strengthening (HDIS). Furthermore, in-situ deformation observation reveals multiple deformation bands in SHM, which delays necking and contributed to ductility in tandem with the transformation induced plasticity (TRIP) effect. The findings highlight a novel approach for the development of SHM with a tunable performance by using LAAM of multiple materials following the configurable architectures. Graphical abstract: Image 1 Highlights: Voxelized architecture material is configurable via additive manufacturing. Voxelized heterostructures combine superior properties from each constitutive material. Voxelized heterostructured material is much stronger than other lamellar materials. Unique deformation bands delay necking and contribute to a good ductility.